IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) PADA PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 TANJUNG MUTIARA - Putri Andini; Bambang Trisno; Helen Triyani (ADIBA : JOURNAL OF EDUCATION, 2024)
So far, the learning system that occurs in elementary schools is still filled with a word view which states that information is a set of realities that must beremembered In addition, most of the learning space situation is still centered on the instructor (focused on educators or teachers) as a source of basic information, and the use of speaking techningues as the main decision of the teaching and learning system. Such a learning teaching situation does not include students in making guestions. To foster a teaching and learning environment that can foster courage, mentality, and inventive and innovative behaviour, it is very important to have a relations hip between the parts of the training such as instructors, students, educational plans, apparatus (learning media) and learning assets, materials, technigues, and assessment tools work together to create usefull learning measures, the Problem Based Learning model is the best decision in today’s learning. The problem is how to apply the issue – based learning model in PAI learning in elementary schools?